Orientation-dependent Pattern Formation in a 1.5D Continuum Model of Curved Dislocations. Issue 1755 (27th February 2015) - Sandfeld, Stefan; Verbeke, Vanessa; Devincre, Benoit
ABSTRACT: Dislocation pattern formation is a phenomenon where during significant plastic deformation dislocations organize themselves into (meta)stable structures. Modeling such systems is a non-trivial task, because the number of interacting dislocations is high, bringing discrete simulation models to their computational limits. Continuum models, although more efficient, generally do not contain sufficient information for a physically detailed representation of such systems. In this paper we show how a continuum dislocation dynamics theory can be used to model idealized pattern formation. Furthermore, we show how discrete dislocation dynamics (DD) simulations can be used to provide physical input for our continuum model.